Short Term Versus Long Term Catheterization after Urogenital Prolapse Surgery - Choudhury, Farzana Rabee; Rashid, Maliha; Rumana, Ratu; Uddin, ABM Zakir; Ava, Nilufar Nasrin (Journal of Shaheed Suhrawardy Medical College, 2012)
Background: Genital prolapse is a common gynaecological problem in developing country like Bangladesh. Objectives: The aim of this study was to evaluate the advantages of short term catheterization in comparison to long term catheterization after genital prolapse surgery. Methodology: This was a prospective analytical cross sectional study being carried out from 1st July 2005 to 30th July 2006 in the Department of Gynaecology & Obstetrics of Sir Salimullah Medical College & Mitford Hospital. A total of 200 patients undergoing genital prolapse surgery were selected for this study. Patients were divided into two groups. In short term catheterization group the urinary catheter was withdrawal within one day after surgery and in the short term catheterization group the catheter was remained in situ for 5 days after surgery. Result: Positive urine culture was found in 16% in long term catheterization group compared with 6% in short term group (P=0.02). Mean duration of hospital stay was 6.98 days in long term catheterization group and 4.68 days in short term catheterization group (P<0.01). Residual volume was more than 200 ml and need for re-catheterization occurred in 3% in group whereas it was 10% in case group (P=0.04). Conclusion: This study permits to conclude that short term catheterization is better than long term catheterization. J Shaheed Suhrawardy Med Coll, 2011;3 (2): 41-43 DOI: http://dx.doi.org/10.3329/jssmc.v3i2.12077